Про посвяту Десятинної церкви - Кабанець, Є.П. (Археологія, 2000)
У статті на засадах узагальнення багатьох літературних джерел подано авторський погляд щодо походження назви первістка культової архітектури Київської Русі — Десятинної церкви. В статье рассмотрен дискуссионный вопрос о полном праздничном названии старейшего каменного храма на Руси — Десятинной церкви. По мнению автора, нет убедительных данных о том, что он посвящался Успению либо Рождеству Богородицы. В то же время на основании астрономических азимутальных расчетов осевой ориентации храма можно установить, что церковь была заложена в день Положения Ризы Богородицы во Влахернах (2 июля). Указанный праздник установлен в память о перенесении в Константинополь посмертных богородичных реликвий (458), которые обладали чудесной градозащитной силой. Такое же значение влахернская символика приобрела и на Руси, воплотив в себе созидательную и охранительную роль христианизации. Именно поэтому Десятинный храм как самый главный оплот духовной и государственной жизни у восточных славян получил такое же название. Однако после строительства в Киеве нового кафедрального собора Святой Софии в 1037—1042 гг. Десятинная церковь утратила свое былое положение, и ее имя перестало употребляться как в обиходе, так и в письменных источниках. The paper considers the debatable problem of the complete celebratory title of the oldest stone temple of the ancient Rus, the Desyatynna church. In the author’s opinion, there is no convincing data on that it was devoted to the Assumption or the Nativity of Our Lady. At the same time, due to the astronomical azimuth calculations of the axial orientation of the temple, it is possible to determine that the church was laid on the day of the Deposition of the Virgin’s Robe at Blachemes (July 2). The indicated holiday was established in memory of the transference of the posthumous Virgin’s relics to Constantinople (458 AD), which had a wonderful protective force. The mentioned Blachemes’ symbolics acquired the same significance also in Rus, embodying the creative and saving role of Christianity by itself. For this reason, the Desyatynna church received the same title as the most important center of spiritual and state life of the East Slavs. However, after the construction of a new cathedral of Sacred Sofia in Kyiv in 1037-1042, the Desyatynna church lost its former position and its name ceased to be used both in common use and in written sources.